Drug delivery of amoxicillin molecule as a suggested treatment for covid-19 implementing functionalized mesoporous SBA-15 with aminopropyl groups - Haneen F. Alazzawi; Issam K. Salih; Talib M. Albayati (Taylor & Francis Group, 2021)
SARS-CoV-2 is a novel coronavirus that was isolated and identified for the first time in Wuhan, China in 2019. Nowadays, it is a worldwide danger and the WHO named it a pandemic. In this investigation, a functionalization post-synthesis method was used to assess the ability of an adapted SBA-15 surface as a sorbent to load the drug from an aqueous medium. Different characterization approaches were used to determine the characterization of the substance before and after functionalization such as X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), nitrogen adsorption-desorption porosimetry (Brunauer-Emmett-Teller) BET surface area analysis, and thermal gravimetric analysis (TGA). Batch adsorption testing was carried out in a single adsorption device to find the impact of multiple variables on the drug amoxicillin charge output. The following parameters were studied: 0-72 hr. contact time, 20-120 mg/l initial concentration, and 20-250 mg of NH2-SBA-15 dose. The outcomes from such experiments revealed the strong influence and behavior of the amino-functional group to increase the drug's load. Drug delivery outcomes studies found that amoxicillin loading was directly related to NH2-SBA-15 contact time and dose, but indirectly related to primary concentration. It was observed that 80% of amoxicillin was loaded while the best release test results were 1 hour and 51%.